Deconstrucciones laberínticas: Lispector y Valenzuela - Nogueira , Fátima R. (Amaltea. Revista de Mitocrítica, 2009)
The basis of this essay is the representation of the labyrinth as a space originated in the obsession to confine the monstrosity (grotesque) as if the human psyche were totally immune to nature as well as to any indication socially considered abnormal. In a symbolic order, the creation of the labyrinth is, thus, understandable as a need to protect the conscious, and bury at the same time in the unconscious the Minotaur present in the human being. Based on these premises I analyze the short stories El búfalo (1960) by Clarice Lispector, and Simetrías (1993) by Luisa Valenzuela. In these texts Pasiphae’s sexual relation with the bull transmutes in a liaison made possible by the gaze. My analysis approaches these three elements—the woman, the beast, and the gaze—focusing on the association between the woman and nature, the consequences of the animal’s representation in the anthropocentric discourse, and, finally, the role of the gaze in both mythical and psychoanalytical fields. These approaches are essential in understanding the need to return to the myth as a way to counteract the anthropocentric discourse as well as a way to inquire about the human nature.